Sources and Determinants of Wholegrain Intake in a Cohort of Australian Children Aged 12–14 Months - Hassan, Amira; Devenish, Gemma; Golley, Rebecca; Ha, Diep; Do, Loc; Scott, Jane (MDPI AG, 2020)
In the first two years of life, exposure to wholegrain foods may help establish life‑long consumption patterns associated with reduced risk of chronic disease, yet intake data are lacking for this age group. This cross‑sectional analysis aimed to determine intakes and food sources of wholegrains in a cohort of 828 Australian children aged 12–14 months, and to identify determinants of wholegrain intake. Three non‑consecutive days of dietary intake data were collected using a 24‑h recall and 2‑day estimated food record. The multiple source method was used to estimate usual wholegrain intake, and the multivariable general linear model procedure used to identify associations between usual wholegrain intake and socio‑demographic determinants. The mean wholegrain intake was 19.5 (±14) g/day, and the major food sources were ready to eat breakfast cereals (40%) breads and bread rolls (26.6%), flours and other cereal grains (9.4%), and commercial infant foods (8.3%). Lower wholegrain intakes were observed for children whose mothers were born in China (p < 0.001) and other Asian countries (p < 0.001), with the exception of India (p = 0.193); those with mothers aged less than 25 years (p = 0.001) and those with two or more siblings (p = 0.013). This study adds to the weight of global evidence highlighting the need to increase children’s intake of foods high in wholegrain, including in the first few years of life.